World class schools : international perspectives on school effectiveness - Reynolds, David, 1949- (RoutledgeFalmer, 2002)
In this book the authors have conducted extensive research and describe what makes a successful school and how this varies in different countries. The book follows the progress of a cohort of 7-year-old children through their schools over a two-year period. It covers schools in the US, Canada, Hong Kong, Taiwan, Australia, the UK, Norway, the Netherlands, and Ireland and:*draw together what it is that the most and least effective schools do in each country*pinpoints what makes 'effective teaching' across the globe*analyses which effectiveness-producing school and teaching factors a.